Predicting initiation of smoking cessation treatment and outcome among adolescents using stressful life events and coping style - Schepis, Ty S. (Subst Abus, 2014)
BACKGROUND: Adolescent smoking is a major public health concern, and current treatments are only somewhat effective in promoting abstinence. One way to improve treatments is to identify psychosocial characteristics that impede cessation, allowing development of targeted treatments. This study examined the influence of two such characteristics, life event stressors and coping, on initiation of cessation treatment and end-of-treatment abstinence status. METHODS: One-hundred five adolescent smokers were eligible to participate in a validated contingency management (CM) and cognitive-behavioral (CBT) cessation treatment; of those, 72 completed at least one treatment session. Data included sociodemographic characteristics, questionnaires assessing past year life events and coping behavior use, and abstinence status at the end of the 4-week treatment. Logistic regression was used to predict treatment initiation and abstinence status, with life event stressor number, coping or their interaction as predictors. RESULTS: Higher levels of cognitive and peer support coping predicted treatment initiation, while life events were unrelated. End-of-treatment abstinence was predicted by higher numbers of life events and greater use of avoidant coping. The interaction of helpless coping and life events also predicted abstinence, with greater increases in helpless coping as total life events rose in abstinent but not non-abstinent participants. Finally, greater use of behavioral coping predicted abstinence in participants exposed to only CM treatment, while lesser use of behavioral coping predicted abstinence in participants receiving combined CM/CBT treatment. CONCLUSIONS: Exposure to life event stressors may promote cessation by forcing use of self-control resources prior to the quit attempt, which may strengthen such resources. Techniques that improve self-control resources may improve cessation outcome, and prevention programs may want to emphasize behavioral coping to improve rates of treatment initiation.